Peningkatan Ekonomi Kreatif Dalam Upaya Pemberdayaan Masyarakat Desa Meranti Di Kecamatan Bilah Hulu - Christine Herawati Limbong; Mulya Rafika; Eva Fitria; Yudi Prayoga (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to explain the improvement and development of a home industry-based creative economy carried out by several academics, namely economics faculty lecturers and several students to the people of Meranti Village, Bilah Hulu District. Where in this study also explains the impact of the creative economy on the income of rural communities, as well as other supporting factors. The method used is qualitative descriptive research, namely by collecting data through observation, interviews, and documentation of the research object. The data analysis technique is using descriptive analysis. The results of research in Meranti Village are: First, the improvement and development of a home industry-based creative economy carried out by lecturers of the Faculty of Economics and Business, Labuhabatu University through the formation of a household business group. Second, increasing the income of the people who participate in the household business group. Third, internal and external factors that support the development carried out by lecturers of the Faculty of Economics and Business, Labuhanbatu University, students, and the Meranti village community in Labuhanbatu Regency.